Abnormal geometry is associated with more severe left ventricular dysfunction in the presence of increased left ventricular mass: a population study. (22nd September 2015) - Chahal, NS; Lim, TK; Jain, P; Chambers, JC; Kooner, JS; Senior, R
Abstract : Background: Remodelling of the left ventricle is associated with adverse cardiovascular events but the mechanism of these effects remains undefined. We investigated the relationship of abnormal left ventricular geometry to left ventricular function in a large cohort of hypertensive subjects. Methods: We studied 1075 hypertensive patients recruited from the London Life Sciences Prospective Population (LOLIPOP) cohort study. Subjects with cardiovascular disease were excluded. All subjects underwent echocardiography (Philips IE33) for the derivation of left ventricular mass index (LVMI). The tissue Doppler parameters of peak myocardial systolic velocity (Sa), diastolic velocity (Ea) and of left atrial pressure (E/Ea) were measured. Using relative wall thickness and LVMI, subjects were categorised as having either: concentric hypertrophy (CH); eccentric hypertrophy (EH); concentric remodelling (CR) or normal geometry. Results: Abnormal left ventricular geometry was present in 424 individuals. Compared with normal left ventricular geometry (table ), peak Sa was impaired only in subjects with CH and EH. Ea was significantly lower and E/Ea higher among subjects with CH, EH and CR. After adjustment for age, race, sex, diabetes mellitus, blood pressure and hypertensive therapy CR remained associated with impaired Ea but not higher left atrial pressure. Subjects with EH (p = 0.004) and CH (p = 0.02) had impaired systolic function, diastolic function (p<0.01) and higher left atrial pressure (p<0.01) compared with normal individuals. Conclusion: In hypertensive individuals, abnormal left ventricular geometry is associated with diastolic dysfunction but only with elevated left atrial pressure and impaired systolic function in the presence of increased left ventricular mass.